Cloning, Expression, and Immunogenicity of Fimbrial-F17A Subunit Vaccine against Escherichia coli Isolated from Bovine Mastitis. (29th November 2017) - Chen, Wei; Liu, Yongxia; Yin, Jinhua; Deng, Youtian; Ali, Tariq; Zhang, Ju; Cheng, Jia; ur Rahman, Sadeeq; Gao, Jian; Han, Bo
Abstract : There is a need to identify and select new promising immunodominant antigens that have the ability to provide protective immunity against E. coli causing bovine mastitis. Recently we showed that f17a was found to be the most prevalent and crucial virulent factor among the pathogenic E. coli isolated from bovine mastitis. Here, in this report, the recombinant F17A based subunit vaccine adjuvant with MF59 was tested for immunogenicity against E. coli in a murine model. The vaccinated mice did not show any abnormal behavioral changes and histopathological lesions after vaccination. The specific antibody level against F17A was significantly higher in MF59-adjuvant-group, and also lasted for longer duration with a significant ( P < 0.01 ) production level of IgG1 and IgG2a. Moreover, we noted higher survival rate in mice injected with F17A-MF59-adjuvant group after challenging with the clinical E. coli strain . Our findings of bacterial clearance test revealed that elimination rate from liver, spleen, and kidney in MF59-adjuvant-group was significantly higher than the control group. Finally, the proportion of CD4+T cells was increased, while CD8+ was decreased in MF59-adjuvant group. In conclusion, the current study reveals the capability of F17A-MF59 as a potential vaccine candidate against pathogenic E. coli causing mastitis in dairy animals.